Pengaruh Metode Pembelajaran Renang Terhadap Kondisi Fisik Siswa Anak Usia 10 Tahun Di Sdn 016 Tanah Merah - Rezki, Rezki; Dupri, Dupri; Islami, Vebi; Anastasia, Elva (Jurnal Sporta Saintika, 2023)
Learning is a process of interaction between students and educators and learning resources in a learning environment. Therefore, the role of the principal as an intermediary connecting the education system, teachers and performance must be perfected. Research objectives: (1) to investigate further about the level of job satisfaction of physical education teachers and (2) to see the effect of the swimming learning method on the physical condition of students in 10-year-old children at SDN 016 Tanah Merah. Research Method: The approach in this study uses the "Pretest Posttest Design". This research involved 10-year-old students of Elementary School (SD) 016 Tanah Merah with a population of grade 4 students. This research involved students of SDN 016 Tanah Merah. To determine the number of samples in this study, researchers used Raosoft software. The results of calculating the sample size obtained for the grade 4 student population are at SDN 016 Tanah Merah. In this study, "Pretest-Posttest Design" acts as the main research instrument. Divided into several aspects such as (i) Multifactor Leadership Questionnaire (MLQ) to get feedback on transformational leadership, and (ii) Job Satisfaction Survey (JSS) to get feedback on teacher job satisfaction. The data obtained in this study were analyzed through descriptive and inferential methods using Smart PLS software.